Activation of a muscle-specific enhancer by the Ski proto-oncogene. - Engert, J C (1995)
In transgenic mice, muscle-specific expression of the c-ski oncogene induces hypertrophy exclusively in a subset of fast muscle fibers. Here we report that regulatory elements from two genes expressed in fast fibers, myosin light chain 1/3 (MLC) and muscle creatine kinase (MCK), were activated when co-transfected with c-ski expression vectors in myoblasts. The expression from the MLC enhancer was reduced when the c-ski oncogene was cotransfected with MyoD into NIH3T3 fibroblasts. Activation of the MLC enhancer by Ski also occurred in vivo, since bigenic progeny generated by mating MLC-CAT and MSV-skitransgenic mice displayed higher CAT activity in their muscles than did the MLC-CAT parental line. Identification of gene targets for the fiber-specific action of the c-ski gene product provides a molecular model that could be used for the further dissection of Ski-induced hypertrophy, both in tissue culture and in vivo.